Evaluation of Bacillus cereus bioinoculants for biocontrol of bacterial leaf blight and growth promotion in shallots - NUR PRIHATININGSIH; ROBI AZIS ARIFIANTO; DINA ISTIQOMAH; IRWANDHI IRWANDHI (Smujo International, 2026)
Abstract. Prihatiningsih N, Arifianto RA, Istiqomah D, Irwandhi. 2026. Evaluation of Bacillus cereus bioinoculants for biocontrol of bacterial leaf blight and growth promotion in shallots. Asian J Agric 10 (1): g100136. https://doi.org/10.13057/asianjagric/g100136. Bacterial leaf blight (Xanthomonas axonopodis pv. allii) is a major disease of shallots (Allium cepa) that requires continuous control. The use of rhizobacterial bioinoculants is an environmentally friendly strategy that serves a dual role, as a biocontrol and a plant growth promoter. This study aims to evaluate the bioinoculant Bacillus cereus in controlling bacterial leaf blight and increasing shallot growth. This research was conducted using a factorial Randomized Block Design (RBD) with 2 factors (cropping pattern and biofertilizer) and 3 replications. All B. cereus treatments inhibited the pathogen's growth in vitro via a bacteriostatic mechanism, with isolate Bm3 producing the largest inhibition zone (14.75 mm). In addition, each B. cereus isolate can produce siderophores and proteases, as well as dissolve phosphate. In field tests, B. cereus treatment can significantly reduce disease development compared to the control. The consortium treatment tended to show the highest efficacy, with low disease intensity (8.33%), control effectiveness of 51.93%, reduced AUDPC (23.50%), and increased nutrient uptake of shallot. These results indicate that the B. cereus bioinoculant, in the form of a consortium, has the potential to be an effective multifunctional inoculant for controlling bacterial leaf blight and enhancing growth in sustainable shallot cultivation.